2018
DOI: 10.1002/cmdc.201800446
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Bioisosteres of Acylhydrazones as Stable Inhibitors of the Aspartic Protease Endothiapepsin

Abstract: Acylhydrazone‐based dynamic combinatorial chemistry (DCC) is a powerful strategy for the rapid identification of novel hits. Even though acylhydrazones are important structural motifs in medicinal chemistry, their further progression in development may be hampered by major instability and potential toxicity under physiological conditions. It is therefore of paramount importance to identify stable replacements for acylhydrazone linkers. Herein, we present the first report on the design and synthesis of stable b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…We hypothesize that the latter might be the cause of chemical instability in aqueous buffer for these compounds. 55 Compounds were also tested for their turbidimetric solubility to establish the maximum concentrations at which each compound could be evaluated in vitro. As shown in Table S2, the solubility of the whole class is good overall; compounds 1−4, 6−8, and 10 did not precipitate at the maximal concentration tested.…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesize that the latter might be the cause of chemical instability in aqueous buffer for these compounds. 55 Compounds were also tested for their turbidimetric solubility to establish the maximum concentrations at which each compound could be evaluated in vitro. As shown in Table S2, the solubility of the whole class is good overall; compounds 1−4, 6−8, and 10 did not precipitate at the maximal concentration tested.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Inspection of the structures reveals that all the unstable compounds (PLZ, SP-2509, and seclidemstat) feature either a hydrazine or an acylhydrazone chemical function. We hypothesize that the latter might be the cause of chemical instability in aqueous buffer for these compounds …”
Section: Resultsmentioning
confidence: 99%
“…In summary, as evidenced by antagonist 10, and as described by Jumde et al 41 replacement by an amide provides a good starting point for further optimization of acylhydrazones.…”
Section: Bioisosteric Replacementmentioning
confidence: 67%
“…Jumde et al recently reported on bioisosteric replacement of the acylhydrazone moiety. 41 Therefore, in an effort to improve on stability and reduce toxicity, we generated a small library of bioisosteric analogues.…”
Section: Bioisosteric Replacementmentioning
confidence: 99%
“…As compared to acylhydrazones, amides are known to be less prone to hydrolysis and subsequent liberation of potentially toxic hydrazides. 28 Moreover, the milder and simple conditions required for the synthesis of amides make them ideal candidates as bioisosteres of acylhydrazones. Similarly, structurally more rigid and hydrolytically stable 1,3,4-oxadiazoles can directly be synthesized from the building blocks of acylhydrazone formation.…”
Section: Resultsmentioning
confidence: 99%